PENGARUH GAYA BELAJAR VISUAL DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA DI KELAS V SDN 13 NANGA PINOH - Natalia, Natalia; Peterianus, Septian; Saputri, Lindai Dwi (STKIP Melawi, 2024)
Abstract : This study aims to determine the effect of visual learning styles in improving student learning outcomes in fifth grade science learning at SDN 13 Nanga Pinoh. This type of research is quantitative research. The subjects in this study were fifth grade students at SDN 13 Nanga Pinoh, totaling 27 students. Data collection techniques used in this study were observation, written tests and documentation. The data analysis technique used is validity test, normality test, hypothesis testing, homogeneity. Student learning outcomes in the posttest are better than the pretest, where the success rate of students in the posttest is higher than the pretest. Based on the results of the pretest and posttest, it can be obtained that student learning outcomes are categorized as good and increase after participating in learning using visual learning styles. Based on the results of hypothesis testing with non-parametric statistical tests with the Wilcoxon test, it is known that the Asymp value. Sig. that is 0.001. Because the value of 0.001 <0.05, it can be concluded that the